Top Incomes in Germany, 1871-2014 - Charlotte Bartels (Journal of Economic History, 2019)
This study provides new evidence on top income shares in Germany from industrialization to the present. Income concentration was high in the nineteenth century, dropped sharply after WWI and during the hyperinflation years of the 1920s, then increased rapidly throughout the Nazi period beginning in the 1930s. Following the end of WWII, German top income shares returned to 1920s levels. The German pattern stands in contrast to developments in France, the United Kingdom, and the United States, where WWII brought a sizeable and lasting reduction in top income shares. Since the turn of the millennium, income concentration in Germany has been on the rise and is today among the highest in Europe. The capital share is consistently positively associated with income concentration, whereas growth, technological change, trade, unions, and top tax rates are positively associated in some periods and negative in others.
Keywords: 330; income distribution; comparison